2021
DOI: 10.1002/da.23225
|View full text |Cite
|
Sign up to set email alerts
|

Transactional patterns of depressive symptoms between mothers and adolescents: The role of emotion regulation

Abstract: Background: Depression is a highly prevalent, debilitating disorder that runs in families. Yet, empirical support for bidirectional mechanisms linking mother-adolescent depression symptoms remains limited. This study examined longitudinal bidirectional relations among emotion regulation (ER) constructs and depressive symptoms among mother-adolescent dyads over time. Pathways for girls and boys were explored separately, given extant research on sex differences in the intergenerational transmission of depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The present study is the first to examine the associations between extrinsic IER and depressive symptoms using a dyadic perspective. Considering that extrinsic IER is an essentially dyadic process (Zaki & Williams, 2013) and that depression development is a highly transactional process (Felton et al, 2021), our results address an important gap in the literature and shed unique light on how parents' and adolescents' use of extrinsic IER is related to adolescent and parent depression. Relatedly, this is one of the first studies to examine extrinsic IER from early to late adolescence (cf., Main et al, 2016), as prior investigations examined either earlier or later periods in development.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 62%
See 1 more Smart Citation
“…The present study is the first to examine the associations between extrinsic IER and depressive symptoms using a dyadic perspective. Considering that extrinsic IER is an essentially dyadic process (Zaki & Williams, 2013) and that depression development is a highly transactional process (Felton et al, 2021), our results address an important gap in the literature and shed unique light on how parents' and adolescents' use of extrinsic IER is related to adolescent and parent depression. Relatedly, this is one of the first studies to examine extrinsic IER from early to late adolescence (cf., Main et al, 2016), as prior investigations examined either earlier or later periods in development.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 62%
“…For example, a study following early adolescents (age 11) and their parents over three years showed that adolescents' depression and anxiety symptoms predicted increases in parent depressive symptoms over time (Johnco et al, 2021). Similarly, a four-year longitudinal study of mid-adolescent (age 15) mother-daughter dyads showed that adolescents' depressive symptoms predict subsequent parental emotion dysregulation (Felton et al, 2021).…”
Section: Extrinsic Ier and Adolescent Depressionmentioning
confidence: 99%
“…Moreover, while maternal depression has been suggested as an important predictor of adolescent depression ( 32 ), the mechanism may be both direct and indirect ( 32 ). Maternal depression influences the social and emotional functioning of adolescents, as adolescents with depressive mothers are easily exposed to emotion regulation difficulties ( 33 ), resulting in poor relationships with their mothers ( 34 ) and poor interpersonal function ( 35 ). Poor interpersonal function may develop emotional vulnerability in adolescents ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…These dynamic processes have significant implications for each family member's psychological well-being. One possible mechanism that may explain these effects is the tendency for children's expressions of emotion and behavior dysregulation (e.g., crying and tantrums) to overwhelm the emotional capacity of their parents, causing distress, and eliciting coercive parenting behaviors (i.e., irritable, critical, and harsh parenting) that in turn exacerbate internalizing and externalizing problems in children (e.g., conduct problems and emotion dysregulation) (Felton et al, 2021;Hails et al, 2018;Schwartz et al, 2011). Decreased family cohesion and increased family conflict resulting from children's internalizing and externalizing problems may also compromise the marital relationship and deplete parents' coping resources, leading to greater parental depression and more negative parenting behaviors (Elgar et al, 2003;Fanti et al, 2013;Gross et al, 2008;Hails et al, 2018;Russell et al, 2019).…”
Section: Reciprocal Effects Of Child and Parent Psychopathologymentioning
confidence: 99%